Work song [large type] - Doig, Ivan (Thorndike Press, 2010)
Morrie Morgan, itinerant teacher, walking encyclopedia, and inveterate charmer, was last seen leaving a one-room schoolhouse in Marias Coulee, the stage he stole in Ivan Doig's The Whistling Season. A decade on, Morrie is back in Montana. Caught up in the mounting clash between the copper-mining company, radical "outside agitators," and the beleaguered miners, he finds a unique way to give a voice to those who truly need one.